Psychological peculiarities of spatio-temporal deprivation and stigmatization of personality - Hoshovska , Daria; Hoshovskiy , Yaroslav (Psychological Prospects Journal, 2021)
Purpose. The article provides a theoretical analysis of the psychological peculiarities of spatio-temporal deprivation (deprived chronotype) and stigmatization of personality. Methods. The methods of scientific theoretical analysis were used for the realization of the research’s purpose: analysis, synthesis, abstract method, generalization. Results. Scientific psychological analysis of the source base has led to the assertion that the problem of spatio-temporal restrictions correlates closely with its stigmatization. The mode of various restrictions blocks a person’s vital activity, and stiffness and oversaturation (as well as deprivation) of personal space bring chaos and ambivalence to the awareness of lifetime. The spatial deprivation complicates and slows down the construction of adequate images of self-identity and harmonious self-construction, as well as blocks personal potential and suppresses individual optimism and the legend of the life path. The deprived person has several problems with personal adaptation, and being in the early stages of ontogenesis and sociogenesis in closed-type educational institutions determines a pessimistic mode of self-awareness. The spatio-temporal deprivation creates an imbalance of a person’s mental world, causes psycho-emotional burnout, and development of excessive anxiety, frustration, and other mental states. It cultivates a child’s suppression and marginality and imposes a certain stigma, which is overcome with varying degrees of success throughout life. Orphans and children living in boarding institutions quite often polarise the world according to the parameter ’friend or foe’ and may experience social exclusion and several other limitations to their psycho-social development. Conclusions. Blocking of spatio-temporal dimensions of the deprived person is a significant psycho-traumatic factor and affects negatively their mental structure, in particular the sensory-emotional, cognitive, and value-behavioral components. Deprivation stigma can cause antisocial and/or deviant personality behavior, therefore, professional revitalization support containing preventive, consultative and corrective, and developmental measures is needed.